Influence of Different Dentin Conditioning Protocols on Bond Strength of a Bioceramic Root Canal Filling - Elif Çiftçioğlu; Güher Barut; Vasfiye Işık; Burçin Arıcan; Işıl Karagöz-Küçükay (University of Zagreb. School of Dental Medicine, 2023)
Objective: Bioceramic-based sealers, in combination with bioceramic-coated gutta-perchas, have become more commonly used in root canal obturation. The present study aimed to assess the influence of laser-assisted dentin conditioning compared with conventional conditioning protocols on the push-out bond strength (PBS) of a bioceramic-based root canal filling. Material and Methods: Sixty extracted mandibular premolars with one root canal were instrumented with EndoSequence rotary files up to size 40/0.04. Four types of dentin conditioning protocols were used: 1) 5.25% NaOCl (con-trol), 2) 17% EDTA+5.25% NaOCl, 3) Diode laser-agitated 17% EDTA+5.25% NaOCl, 4) Er,Cr:YSGG laser irradiation+5.25% NaOCl. Teeth were obturated using the single-cone technique with Endo-Sequence BC sealer+BC points (EBCF). After having obtained 1-mm-thick horizontal slices from the apical, middle and coronal root thirds, push-out test was carried out, and failure modes were de-termined. The data were analyzed by two-way analysis of variance and Tukey's test with a significance level of p<0.05. Results: The apical segments showed the highest PBS in all groups (p<0.05). In the apical segments, EDTA+NaOCl and diode laser agitated EDTA increased the PBS compared to the control (p=0.0001) and Er, Cr: YSGG laser (p=0.011 and p=0.027, respectively) groups. Both laser-used groups revealed significantly higher PBS values in the middle and coronal segments than EDTA+NaOCl (p<0.05). The bond failure was predominantly cohesive without any significant difference among the groups (p>0.05). Conclusions: Laser-assisted dentin conditioning had distinct effects on the PBS of the EBCF at different root segments. Although Er, Cr: YSGG was ineffective in the apical segments, generally, laser-assisted dentin conditioning affected PBS more favorably than conventional irrigation groups, with a more pronounced effect in the diode laser-agitated EDTA group.